On the Design and Implementation of Real-Time Resource Access Protocols - dos Santos, Lucas Matheus; Gracioli, Giovani; Kloda, Tomasz; Caccamo, Marcos (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC), 2020)
Real-time operating systems (RTOS) should support resource access protocols to bound the maximum delay incurred by priority inversions. The implementation of such protocols must be lightweight because its performance affects the system schedulability. In this paper, we present an object-oriented design of real-time resource access protocols for single- and multi-core systems aiming at reducing the run-time overhead and increasing code re-usability. We implement the proposed design in an RTOS and measure the memory footprint and run-time overhead of the implementation in a modern processor. By applying the obtained overhead into the schedulability analysis of six protocols for synthetically generated task sets, our results indicate that proper implementation of resource access protocols has a low impact on the schedulability of real-time tasks.